Bed form-induced hyporheic exchange and geochemical hotspots. (October 2021) - Behzadi, Faranak; Wallace, Corey D.; Ward, Dylan; Zhou, Haiyan; Versteeg, Roelof; Soltanian, Mohamad Reza
Highlights: Solute exchange and solute penetration are higher for out-of-phase bed forms. Reaction rate and size of reaction zone are higher for out-of-phase bed forms. Bed form controls the size of reaction zone in highly conductive sediments. Pressure fluctuations influence the reaction zone size and the reaction rates. Abstract: Small-scale bed form topographies control hyporheic exchange and biogeochemical processes within aquatic sediments, which ultimately affect water quality and nutrient cycling at the watershed scale. The impact of three-dimensional and small-scale bed form topographies on hyporheic exchange and solute mixing is investigated in the present work. The effect of bed form morphologies on the development of zones of enhanced reaction rates (i.e., hotspots) is also studied. A computational fluid dynamics model to simulate river flow over bed forms is combined with a subsurface flow and multicomponent reactive solute transport model. A wide variety of bed form topographies are generated using geometric models by varying parameters controlling curvature as well as bed form wavelength and amplitude. The results in this research suggest that out-of-phase bed forms generate more complex hyporheic flow patterns which reduce the efficiency of solute transformations. Higher phase shifts in bed form shapes result in overall higher average velocity, larger zones of enhanced pressure and reaction rates, and higher amounts of solute exchange. Moreover, the bed form shapes control the reaction process for a wide range of sediment conductivities. This study advances the understanding of the effects of complex and small scale morphological features on hyporheic exchange processes including the rate and spatio-temporal distribution of reaction hotspots.